ZNACZENIE AKTÓW JEDNOSTRONNYCH DLA WSPÓŁCZESNYCH STOSUNKÓW POLSKO-NIEMIECKICH - Sandorski, Jan (Wydział Prawa i Administracji UAM, 2006)
The author claims that there are two unilateral acts which are of fundamental importance for further development of Polish-German relations: the declaration of the German Chancellor Gerhard Schroder of 1 August 2004, and the declaration of the Polish People’s Republic of 23 August 1953 in which Poland resigned from its claims for war reparations. In the second part of the paper the author argues with the thesis proposed by prof. Eckart Klein who is of an opinion that the validity of Chancellor Schroder’s statement is questionable as it is contradictory to ius cogens applying to crimes against humanity (art. 50 of the 1st Geneva Convention of 12 August 1949). The author’s view is that Poland’s overtaking of German possessions was not an unlawful and lawlessness act because it was performed pursuant to the will of the Allies expressed i.a. in Potsdam Conference’s Declaration, and was the consequence of the manner in which Germany started, carried out and ended the war. The author also emphasises the importance of the law of equity and expresses a hope that if there arises an international dispute, the International Court of Justice will construe Potsdam Declaration in such a spirit. In the remaining part of the paper the author claims that Poland’s resignation from reparation claims in 1953 might be pronounced invalid due to the fact that it was made under duress exercised by the Soviet Union on Poland (coal blackmail).) Consequently, Poland’s sovereignty was violated, the result of which was a statement of will characterised with absolute invalidity. The conclusion is that every tension arising from unilateral statements or acts should be solved through friendly diplomatic relations between neighbouring states.
THE SIGNIFICANCE OF UNILATERAL ACTS FOR CONTEMPORARY POLISH-GERMAN RELATIONS